Decision theory : principles and approaches - Parmigiani, G. (Giovanni); Inoue, Lurdes Y. T. (Lurdes Yoshiko Tani), 1970-; Lopes, Hedibert Freitas (John Wiley & Sons, 2009)
Decision theory provides a formal framework for making logical choices in the face of uncertainty. Given a set of alternatives, a set of consequences, and a correspondence between those sets, decision theory offers conceptually simple procedures for choic.